Performance evaluation of S-PET, a compact, high sensitivity and high resolution small animal PET prototype - Yang, Hang; He, Wen; Zhao, Xin; Li, Guangming; Zhao, Yangyang; Huang, Wenjie; Huang, Yong; Niu, Ming; Liang, Ying; Gu, Zheng (LangTaoSha Preprint Server, 2026)
S-PET is a compact, high sensitivity and high resolution small animal PET prototype developed at Shenzhen Bay Laboratory (SZBL). The S-PET system employs a phoswich depth of interaction (DOI) detector design, which also allows identification of the large majority of the cross layer crystal scatter (CLCS) events. This work evaluates its performance characteristics following the National Electrical Manufacturers Association (NEMA) NU4-2008 protocol. The S-PET consists of twenty flat panel type detectors arranged in two rings. The inner diameter is 80 mm and the axial field of view (FOV) is 104.5 mm. Each detector is comprised of two layers of phoswich scintillator crystal arrays, an oblique edge cut glass lightguide and two multipixel photon counter (MPPC) arrays. The front (annihilation photon entrance) layer is a 30 × 60 pixelated cerium doped lutetium yttrium orthosilicate (LYSO) scintillator array with individual crystals measuring 0.79 × 0.79 × 5 mm3. The back (towards the MPPCs) layer is a 20 × 40 pixelated bismuth germanate (BGO) scintillator array with individual crystals measuring 1.22 × 1.22 × 7.5 mm3. For energy windows 350-650 keV, the peak absolute sensitivity at the center of the FOV was 14.9% including CLCSevents, and 11.9% excluding CLCS events. The average system energy resolution derived by averaging the individual crystal spectra was 11.2% ± 3.1% for LYSO and 28.3% ± 5.8% for BGO. The 3D ordered-subsets expectation maximization (OSEM) reconstructed image with spatially variant point spread function (PSF) modeling of a point source in air, ranged from 0.66 mm to 1.09 mm, with an average value of 0.78 ± 0.10 mm at all measured locations. The peak noise equivalent count rate (NECR) and scatter fractions were 237.4 kcps at 11.9 MBq and 13.0% for the mouse-sized phantom, and 110.3 kcps at 11.9 MBq and 23.3% for the rat-sized phantom. For the NEMA image quality phantom, the uniformity was 6.3%, and the spillover ratios measured in the water- and air-filled cold region chambers were 11.1% and 7.9%, respectively. The recovery coefficients (RC) ranged from 0.36 to 0.89. The comprehensive results demonstrate that S-PET developed at SZBL possesses high spatial resolution and high sensitivity, which meets the requirements of preclinical research, such as mouse and rat imaging.